A 3′‐end capture sequencing method for high‐throughput targeted gene expression profiling. Issue 9 (24th May 2022) - de Bony, Eric; Gysens, Fien; Yigit, Nurten; Anckaert, Jasper; Everaert, Celine; Vanden Eynde, Eveline; Verniers, Kimberly; van Snippenberg, Willem; Trypsteen, Wim; Mestdagh, Pieter
Abstract: Molecular phenotyping through shallow 3′‐end RNA‐sequencing workflows is increasingly applied in the context of large‐scale chemical or genetic perturbation screens to study disease biology or support drug discovery. While these workflows enable accurate quantification of the most abundant genes, they are less effective for applications that require expression profiling of low abundant transcripts, like long noncoding RNAs (lncRNAs), or selected gene panels. To tackle these issues, we describe a workflow combining 3′‐end library preparation with 3′‐end hybrid capture probes and shallow RNA‐sequencing for cost‐effective, targeted quantification of subsets of (low abundant) genes across hundreds to thousands of samples. To assess the performance of the method, we designed a capture probe set for more than 100 mRNA and lncRNA target genes and applied the workflow to a cohort of 360 samples. When compared to standard 3′‐end RNA‐sequencing, 3′‐end capture sequencing resulted in a more than 200‐fold enrichment of target gene abundance while conserving relative intergene and intersample abundances. 3′‐end RNA capture sequencing enables accurate targeted gene expression profiling at extremely shallow sequencing depth. Graphical Abstract and Lay Summary: Shallow 3'‐end RNA‐sequencing allow large numbers of samples to be profiled. Unfortunately, sequencing reads generated by these methods will only cover the most abundant genes. Using 3'‐end hybridization probes we developed a capture‐sequencing approach to maximize read allocation to a subset of targets of interest. This approach enables accurate targeted gene expression profiling at extremely shallow sequencing depth.